Revision of Pseudastenus Bernhauer, synonym with Xenasterides Newton and six new species (Coleoptera, Staphylinidae, Paederinae) - Busanello, Dilson G. C.; Irmler, Ulrich; Caron, Edilson (Zootaxa, 2020)
The genus Xenasterides Newton, 2017 is considered here as a junior synonym of Pseudastenus Bernhauer, 1933, both monotypic and Neotropical genera of Paederinae (Staphylinidae). A thorough description of the genus is provided. The species Pseudastenus barretoi Bernhauer, 1933 and P. plaumanni (Bierig, 1939) are redescribed and illustrated, six new species are described, and a dichotomous key is available for species. These new species are: P. amazonicus, P. ferrugineus, P. latus, P. oculatus, P, ribeirocostae, and P. schubarti.